2009
DOI: 10.1073/pnas.0902873106
|View full text |Cite
|
Sign up to set email alerts
|

A tumor suppressive coactivator complex of p53 containing ASC-2 and histone H3-lysine-4 methyltransferase MLL3 or its paralogue MLL4

Abstract: ASC-2, a multifunctional coactivator, forms a steady-state complex, named ASCOM (for ASC-2 COMplex), that contains the histone H3-lysine-4 (H3K4)-methyltransferase MLL3 or its paralogue MLL4. Somewhat surprisingly, given prior indications of redundancy between MLL3 and MLL4, targeted inactivation of the MLL3 H3K4-methylation activity in mice is found to result in ureter epithelial tumors. Interestingly, this phenotype is exacerbated in a p53 ؉/؊ background and the tumorigenic cells are heavily immunostained fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
195
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(213 citation statements)
references
References 42 publications
15
195
2
1
Order By: Relevance
“…H3K4 methylation is primarily localized in the promoter and regulatory regions of genes. Some transcription factors, such as Menin, LEDGF, HCF1/2, E2F, NFE2, p53, and c-Myb, have been shown to interact with MLL family members, which could lead to methylation of H3K4 in a locus-or DNA sequence-specific manner [16,17,[25][26][27][28][29]. A recent study by our group identified a physical and functional interaction between RUNX1 and MLL, and showed that both are required for maintenance of the H3K4me3 mark at two critical regulatory regions of the RUNX1 target gene PU.1 locus [30].…”
Section: Mll and Its Role In Normal Hematopoiesismentioning
confidence: 99%
“…H3K4 methylation is primarily localized in the promoter and regulatory regions of genes. Some transcription factors, such as Menin, LEDGF, HCF1/2, E2F, NFE2, p53, and c-Myb, have been shown to interact with MLL family members, which could lead to methylation of H3K4 in a locus-or DNA sequence-specific manner [16,17,[25][26][27][28][29]. A recent study by our group identified a physical and functional interaction between RUNX1 and MLL, and showed that both are required for maintenance of the H3K4me3 mark at two critical regulatory regions of the RUNX1 target gene PU.1 locus [30].…”
Section: Mll and Its Role In Normal Hematopoiesismentioning
confidence: 99%
“…PHD and SET domain proteins are chromatin regulators, and several are altered in cancer (Saha et al, 1995). Inactivation of MLL3 in mice results in epithelial tumor formation, suggesting that MLL3 functions as a tumor-suppressor gene (Lee et al 2009). In addition, MLL3 has been reported to be frequently deleted in myeloid leukemia (Ruault et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This complex called ASCOM interacts with p53 and is required for expression of p53-target genes in response to DNA damage. These results indicate a role of MLL3 in the DNA damage response pathway through p53 activation (31). The down regulation of MLL3 in larynx cancer may therefore impair the DNA damage response contributing to the proliferation of cancer cells.…”
Section: Discussionmentioning
confidence: 83%